Positive electrode material composition, positive electrode sheet, battery, and power using device
Patent Information
- Application Number
- CN202410254207.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-03-06
AI Technical Summary
[0031]由此,采用微米级的正极材料A与亚微米或纳米级的正极材料B混合制备正极极片。当正极材料A在正极材料总重中占比大于等于50%且小于100%时,正极材料B的Dv50粒径在上述范围内解决了材料颗粒过小、微粉过多的问题,正极材料A的Dv50粒径与所述正极材料B的Dv50粒径的比例在上述范围内减少了冷压过程中极片表面小颗粒粘在压辊上的数量,正极材料A的包覆层重量占比在上述范围内增加了材料表面的粗糙度,提高了材料颗粒间的相互粘结性,降低了冷压过程中的粘辊程度,从而提升了正极极片的实际厚度,进而提升了电池的容量。当正极材料A在正极材料总重中占比大于0且小于50%时,不存在冷压粘辊问题。
Smart Images

Figure CN120613390B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, and more particularly to a positive electrode material composition, a positive electrode sheet, a battery, and an electrical device. Background Technology
[0002] In recent years, with the increasingly wide range of applications, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. Due to the significant development of secondary batteries, higher requirements have been placed on the performance of the positive electrode. Summary of the Invention
[0003] This application was made in view of the above-mentioned problems, and its object is to provide a positive electrode material composition, a positive electrode sheet, a battery, and an electrical device. Using the positive electrode material composition of this application, the degree of roller sticking during the cold pressing process is reduced, the actual thickness of the positive electrode sheet is increased, and thus the battery capacity is improved.
[0004] To achieve the above objectives, a first aspect of this application provides a cathode material composition comprising cathode material A and cathode material B, wherein cathode material A and cathode material B are independently single-crystal materials or quasi-single-crystal materials;
[0005] When the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the particle size of the positive electrode material A particles is in the micrometer range, the particle size of the positive electrode material B particles is in the submicrometer or nanometer range, the ratio of the Dv50 particle size of the positive electrode material A particles to the Dv50 particle size of the positive electrode material B particles is 3.5-11.25, the Dv50 particle size of the positive electrode material B particles is 0.4-1μm, and the positive electrode material A includes a core and one or more coating layers covering the core, the total weight of the coating layers accounts for 1800ppm-4000ppm of the weight of the positive electrode material A;
[0006] When the weight percentage of the positive electrode material A in the positive electrode active material composition is greater than 0 and less than 50%, the particle size of the positive electrode material A particles is in the micrometer range, and the particle size of the positive electrode material B particles is in the submicrometer or nanometer range.
[0007] Therefore, a positive electrode sheet is prepared by mixing micron-sized positive electrode material A with submicron or nano-sized positive electrode material B. When the proportion of positive electrode material A in the total weight of the positive electrode material is greater than or equal to 50% and less than 100%, the Dv50 particle size of positive electrode material B, within the above range, solves the problem of excessively small material particles and excessive micro powder. The ratio of the Dv50 particle size of positive electrode material A to that of positive electrode material B, within the above range, reduces the number of small particles on the electrode surface sticking to the pressure roller during cold pressing. The weight proportion of the coating layer of positive electrode material A, within the above range, increases the surface roughness of the material, improves the mutual adhesion between material particles, reduces the degree of sticking to the roller during cold pressing, thereby increasing the actual thickness of the positive electrode sheet and thus improving the battery capacity. When the proportion of positive electrode material A in the total weight of the positive electrode material is greater than 0 and less than 50%, there is no problem of sticking to the roller during cold pressing.
[0008] In any embodiment, when the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the Dv50 particle size of the positive electrode material A particles is 3.5-4.5 μm.
[0009] Therefore, when the proportion of positive electrode material A in the total weight of positive electrode material is greater than or equal to 50% and less than 100%, the Dv50 particle size of positive electrode material A within the above range reduces the number of particles on the electrode surface adhering to the pressure roller during cold pressing, thereby increasing the actual thickness of the positive electrode sheet.
[0010] In any embodiment, when the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the BET specific surface area of the positive electrode material A is 0.6-0.9 m². 2 / g, and / or, the BET specific surface area of the cathode material B is 9.4-15.5m². 2 / g.
[0011] Therefore, by using the above-mentioned cathode material A and cathode material B, the BET specific surface area is reduced, the number of excessively small particles and micro powders is reduced, the mutual adhesion between material particles is improved, the degree of sticking to the rollers during the cold pressing process is reduced, thereby increasing the actual thickness of the cathode sheet and improving the battery capacity.
[0012] In any embodiment, when the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%,
[0013] The ratio of the Dv50 particle size of the positive electrode material A particles to the Dv50 particle size of the positive electrode material B particles is 3.5-5; and / or,
[0014] The Dv50 particle size of the cathode material B particles is 0.8-1 μm; and / or,
[0015] The total weight of the coating layer accounts for 2000ppm-2800ppm of the weight of the cathode material A; and / or,
[0016] The positive electrode material A particles have a Dv50 particle size of 3.5-4 μm; and / or,
[0017] The BET specific surface area of the cathode material A is 0.74-0.9 m². 2 / g, and / or,
[0018] The BET specific surface area of the cathode material B is 11-15.5 m² / g.
[0019] In any embodiment, the positive electrode material A is a layered positive electrode material, and / or the positive electrode material B is a polyanion positive electrode material.
[0020] In any embodiment, the positive electrode material A includes a core and one or more coating layers covering the core, the core comprising the compound Li. a Ni b Co c M1 a M2 e O f R g The one or more coating layers independently comprise one or more of oxides and phosphates; wherein, 0.75≤a≤1.2, 0<b<1, 0<c<1, 0<d<1, 0≤e≤0.2, 1≤f≤2.5, 0≤g≤1, f+g≤3, M1 comprises one or more elements from Group IIIA and Group VIIB, M2 comprises one or more elements from Group IIA, Group VA, Group IB, Group IIB, Group IIIB, Group IVB, Group VB, Group VIB, and Group VIII, and R comprises one or more elements from Group VA, Group VIA, and Group VIIA.
[0021] In any embodiment, when the weight percentage of the positive electrode material A in the positive electrode active material composition is greater than 0 and less than 50%, the positive electrode material A includes the compound Li. a Ni b Co c M1 d M2 e O f R gWherein, 0.75≤a≤1.2, 0<b<1, 0<c<1, 0<d<1, 0≤e≤0.2, 1≤f≤2.5, 0≤g≤1, f+g≤3, M1 includes one or more elements from groups IIIA and VIIB, M2 includes one or more elements from groups IIA, VA, IB, IIB, IIIB, IVB, VB, VIB, and VIII, and R includes one or more elements from groups VA, VIA, and VIIA.
[0022] In any embodiment, the positive electrode material B includes the compound Li. 1+x Mn 1-y A y P 1-z Q z O4, wherein -0.100≤x≤0.100, 0.001≤y≤0.800, 0.001≤z≤0.100, A includes one or more elements from families IA, IIA, IIIA, IVA, VA, IIB, IVB, VB, VIB, and VIII, and Q includes one or more elements from families IIIA, IVA, VA, VIA, and VIIA.
[0023] In any embodiment, the positive electrode material B includes a core and one or more coating layers covering the core, the core comprising the compound Li. 1+x Mn 1-y A y P 1-z Q z O4, wherein the one or more coating layers independently comprise one or more of pyrophosphate, phosphate, and carbon; wherein -0.100≤x≤0.100, 0.001≤y≤0.800, 0.001≤z≤0.100, A comprises one or more elements from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IVB, Group VB, Group VIB, and Group VIII, and Q comprises one or more elements from Group IIIA, Group IVA, Group VA, Group VIA, and Group VIIA.
[0024] In any implementation, M1 includes one or more elements selected from Mn and Al; and / or,
[0025] The M2 includes one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb; and / or,
[0026] The R includes one or more elements selected from N, F, S, and Cl; and / or,
[0027] One or more coating layers in the positive electrode material A independently include one or more of Al2O3, ZrO2, TiO2, and Li3PO4; and / or,
[0028] The A includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge; and / or,
[0029] The Q includes one or more elements selected from B, Si, N, S, F, Cl, and Br.
[0030] A second aspect of this application also provides a positive electrode sheet, comprising the positive electrode material composition of the first aspect of this application.
[0031] Therefore, a positive electrode sheet is prepared by mixing micron-sized positive electrode material A with submicron or nano-sized positive electrode material B. When the proportion of positive electrode material A in the total weight of the positive electrode material is greater than or equal to 50% and less than 100%, the Dv50 particle size of positive electrode material B, within the above range, solves the problem of excessively small material particles and excessive micro powder. The ratio of the Dv50 particle size of positive electrode material A to that of positive electrode material B, within the above range, reduces the number of small particles on the electrode surface sticking to the pressure roller during cold pressing. The weight proportion of the coating layer of positive electrode material A, within the above range, increases the surface roughness of the material, improves the mutual adhesion between material particles, reduces the degree of sticking to the roller during cold pressing, thereby increasing the actual thickness of the positive electrode sheet and thus increasing the battery capacity. When the proportion of positive electrode material A in the total weight of the positive electrode material is greater than 0 and less than 50%, there is no problem of sticking to the roller during cold pressing.
[0032] In any embodiment, the positive electrode sheet further includes a binder;
[0033] When the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the weight percentage of the binder in the positive electrode sheet is 1.2%-1.8%.
[0034] When the weight percentage of the positive electrode material A in the positive electrode active material composition is greater than 0 and less than 50%, the weight percentage of the binder in the positive electrode sheet is 1.9%-2.3%.
[0035] Therefore, when the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, using the above-mentioned weight percentage of the binder is beneficial to improving the brittleness of the positive electrode sheet while maintaining the interparticle bonding effect. When the weight percentage of the positive electrode material A in the positive electrode active material composition is greater than 0 and less than 50%, increasing the amount of binder to the above range can improve the bonding effect between the two positive electrode material particles and increase the actual thickness of the positive electrode sheet.
[0036] A third aspect of this application provides a battery comprising a positive electrode material composition of the first aspect of this application or a positive electrode sheet of the second aspect of this application.
[0037] A fourth aspect of this application provides an electrical device including the battery of the third aspect of this application. Attached Figure Description
[0038] Figure 1 This is a schematic diagram of a battery cell according to one embodiment of this application.
[0039] Figure 2 yes Figure 1 An exploded view of a battery cell according to one embodiment of this application is shown.
[0040] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0041] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0042] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.
[0043] Figure 6 This is a schematic diagram of an electrical device in which a single battery cell is used as a power source according to one embodiment of this application.
[0044] Explanation of reference numerals in the attached figures:
[0045] 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation
[0046] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the negative electrode active material and its manufacturing method, positive electrode sheet, negative electrode sheet, battery cell, battery module, battery pack, and power supply device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0047] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0048] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0049] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0050] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0051] Unless otherwise specified, "micrometer scale" in this application refers to a size greater than or equal to 1 μm and less than or equal to 10 μm.
[0052] Unless otherwise specified, "submicron" in this application refers to a size greater than or equal to 0.5 μm and less than 1 μm.
[0053] Unless otherwise specified, "nanoscale" in this application refers to a size of less than 500 nm.
[0054] [Battery cell]
[0055] A battery cell, also known as a rechargeable battery or storage battery, is a battery that can be recharged after being discharged to activate the active materials and continue to be used.
[0056] Typically, a battery cell includes a positive electrode, a negative electrode, a separator, and an electrolyte. During charging and discharging, active ions (such as lithium ions) repeatedly insert and extract between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing active ions to pass through. The electrolyte, also positioned between the positive and negative electrodes, mainly serves to conduct active ions.
[0057] [Positive Electrode Material Composition]
[0058] One embodiment of this application provides a cathode material composition, including cathode material A and cathode material B, wherein cathode material A and cathode material B are independently single-crystal materials or quasi-single-crystal materials;
[0059] When the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100% (e.g., 50%, 60%, 70%, 80%, 90%, 100%, or any range of the above values), the particle size of the positive electrode material A particles is in the micrometer range, the particle size of the positive electrode material B particles is in the submicrometer or nanometer range, and the ratio of the Dv50 particle size of the positive electrode material A particles to the Dv50 particle size of the positive electrode material B particles is 3.5-11.25 (e.g., 3.5, 4, 4.5, 4.88, 5, 5.5, 6, 6.3, 6.4, 6.5, 6.9, 7, 7.1, 7.5, 7.64, 8, 8.1, 8.2, 8.5, 9.0, 9.5, 9.75, 10, 10.5, 11, 11.25, or any range of the above values). The positive electrode material B particles have a Dv50 particle size of 0.4-1μm (e.g., 0.4μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 0.95μm, 1μm or any range of the above values), and the positive electrode material A includes a core and one or more coating layers covering the core, and the total weight of the coating layers accounts for 1800ppm-4000ppm of the weight of the positive electrode material A (e.g., 1800ppm, 1900ppm, 2000ppm, 2200ppm, 2500ppm, 2800ppm, 3000ppm, 3300ppm, 3500ppm, 4000ppm or any range of the above values).
[0060] When the weight percentage of the positive electrode material A in the positive electrode active material composition is greater than 0 and less than 50%, the particle size of the positive electrode material A particles is in the micrometer range, and the particle size of the positive electrode material B particles is in the submicrometer or nanometer range.
[0061] The applicant has discovered that when micron-sized single crystal / quasi-single crystal particles are mixed with submicron-sized or nano-sized single crystal / quasi-single crystal particles to prepare positive electrode sheets, and the proportion of micron-sized particles in the total weight of the positive electrode material is greater than or equal to 50% and less than 100%, the cold pressing process is prone to roller sticking, which leads to a reduction in the actual thickness of the positive electrode sheet, thereby causing a decrease in the battery capacity.
[0062] Although the mechanism is not yet clear, the applicant unexpectedly discovered that using a mixture of micron-sized cathode material A and submicron or nano-sized cathode material B to prepare cathode sheets: When cathode material A accounts for 50% to 100% of the total weight of the cathode material, the Dv50 particle size of cathode material B, within the aforementioned range, solves the problem of excessively small particles and excessive micropowder. The ratio of the Dv50 particle size of cathode material A to that of cathode material B, within the aforementioned range, reduces the number of small particles adhering to the pressure rollers on the electrode surface during cold pressing. The weight percentage of the coating layer of cathode material A, within the aforementioned range, increases the surface roughness of the material, improves the mutual adhesion between material particles, and reduces the degree of roller adhesion during cold pressing, thereby increasing the actual thickness of the cathode sheet and thus improving the battery capacity. When cathode material A accounts for 0% to 50% of the total weight of the cathode material, there is no problem of roller adhesion during cold pressing.
[0063] In some embodiments, in any embodiment, when the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the Dv50 particle size of the positive electrode material A particles is 3.5-4.5 μm, for example, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm or any range of the above values.
[0064] Therefore, when the proportion of positive electrode material A in the total weight of positive electrode material is greater than or equal to 50% and less than 100%, the Dv50 particle size of positive electrode material A within the above range reduces the number of particles on the electrode surface adhering to the pressure roller during cold pressing, thereby increasing the actual thickness of the positive electrode sheet.
[0065] In some embodiments, when the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the BET specific surface area of the positive electrode material A is 0.6-0.9 m². 2 / g (e.g., 0.6m) 2 / g, 0.65m 2 / g, 0.68m 2 / g, 0.7m 2 / g, 0.71m 2 / g, 0.73m 2 / g, 0.74m 2 / g, 0.78m 2 / g, 0.8m 2 / g, 0.85m 2 / g, 0.9m 2 / g or any of the above values), and / or, the BET specific surface area of the positive electrode material B is 9.4-15.5m².2 / g (e.g., 9.4m) 2 / g、11m 2 / g, 11.5m 2 / g、12m 2 / g, 12.5m 2 / g、13m 2 / g, 13.5m 2 / g, 13.6m 2 / g, 13.8m 2 / g、14m 2 / g, 14.1m 2 / g, 14.6m 2 / g, 15m 2 / g, 15.5m 2 / g or any range of the above values).
[0066] Therefore, by using the above-mentioned cathode material A and cathode material B, the BET specific surface area is reduced, the number of excessively small particles and micro powders is reduced, the mutual adhesion between material particles is improved, the degree of sticking to the rollers during the cold pressing process is reduced, thereby increasing the actual thickness of the cathode sheet and improving the battery capacity.
[0067] In some embodiments, when the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%,
[0068] The ratio of the Dv50 particle size of the positive electrode material A particles to the Dv50 particle size of the positive electrode material B particles is 3.5-5; and / or,
[0069] The Dv50 particle size of the cathode material B particles is 0.8-1 μm; and / or,
[0070] The total weight of the coating layer accounts for 2000ppm-2800ppm of the weight of the cathode material A; and / or,
[0071] The positive electrode material A particles have a Dv50 particle size of 3.5-4 μm; and / or,
[0072] The BET specific surface area of the cathode material A is 0.74-0.9 m². 2 / g, and / or,
[0073] The BET specific surface area of the cathode material B is 11-15.5 m². 2 / g.
[0074] The Dv50 particle size was tested using conventional methods in the field; for example, after dispersing the sample, it was tested using a laser particle size analyzer.
[0075] The BET specific surface area is tested using conventional methods in the field; for example, the adsorption-desorption curve is tested using nitrogen adsorption specific surface area analysis, and then calculated using the BET (Brunauer Emmett Teller) method. In the nitrogen adsorption specific surface area analysis, the sample is vacuum dried, filled with liquid nitrogen, and placed in a test tube. Adsorption-desorption curves with a relative pressure P / P0 of 0–0.99 are plotted using a specific surface area and porosity analyzer.
[0076] In some embodiments, the positive electrode material A is a layered positive electrode material, and / or the positive electrode material B is a polyanionic positive electrode material.
[0077] Those skilled in the art know that layered cathode materials usually refer to layered ternary cathode materials.
[0078] In some embodiments, the cathode material A includes a core and one or more coating layers covering the core, the core comprising the compound Li. a Ni b Co c M1 d M2 e O f R g The one or more coating layers independently comprise one or more of oxides and phosphates; wherein 0.75 ≤ a ≤ 1.2 (e.g., 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.2, or any range of the above values), 0 < b < 1 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9, 0.99, or any range of the above values), 0 < c < 1 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9, 0.99, or any range of the above values), and 0 < d < 1 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6). The ranges are defined as follows: M1 includes one or more elements from Groups IIIA and VIIB; M2 includes one or more elements from Groups IIA, VA, IB, IIB, IIIB, IVB, VB, VIB, and VIII; and R includes one or more elements from Groups VA, VIA, and VIIA.
[0079] In some embodiments, when the weight percentage of the positive electrode material A in the positive electrode active material composition is greater than 0 and less than 50%, the positive electrode material A includes the compound Li. a Ni b Co c M1 d M2 e O f R g Wherein, 0.75≤a≤1.2 (e.g., 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.2, or any range of the above values), 0<b<1 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9, 0.99, or any range of the above values), 0<c<1 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9, 0.99, or any range of the above values), 0<d<1 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9, 0.9). 9 or any of the above values), 0≤e≤0.2 (e.g., 0, 0.1, 0.2 or any of the above values), 1≤f≤2.5 (e.g., 1, 1.5, 2, 2.5 or any of the above values), 0≤g≤1 (e.g., 0, 0.5, 1 or any of the above values), f+g≤3 (e.g., 1, 2, 3 or any of the above values), M1 includes one or more elements from Group IIIA and Group VIIB, M2 includes one or more elements from Group IIA, Group VA, Group IB, Group IIB, Group IIIB, Group IVB, Group VB, Group VIB and Group VIII, and R includes one or more elements from Group VA, Group VIA and Group VIIA.
[0080] Those skilled in the art will know that polyanionic cathode materials generally refer to phosphate cathode materials, such as lithium manganese iron phosphate.
[0081] In some embodiments, the cathode material B includes the compound Li. 1+x Mn 1-y A y P 1-z Q zO4, wherein -0.100≤x≤0.100 (e.g., x is a range of -0.1, -0.05, 0, 0.05, 0.1, or any of the above values), 0.001≤y≤0.800 (e.g., y is a range of 0.001, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or any of the above values), 0.001≤z≤0.100 (e.g., z is a range of 0.001, 0.005, 0.01, 0.05, 0.1, or any of the above values), wherein A includes one or more elements from families IA, IIA, IIIA, IVA, VA, IIB, IVB, VB, VIB, and VIII, and Q includes one or more elements from families IIIA, IVA, VA, VIA, and VIIA.
[0082] In some embodiments, the cathode material B includes a core and one or more coating layers covering the core, the core comprising the compound Li. 1+x Mn 1-y A y P 1-z Q z O4, wherein the one or more coating layers independently comprise one or more of pyrophosphate, phosphate, and carbon; wherein -0.100 ≤ x ≤ 0.100 (e.g., x is a range of -0.1, -0.05, 0, 0.05, 0.1, or any of the above values), and 0.001 ≤ y ≤ 0.800 (e.g., y is a range of 0.001, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or any of the above values). The range is 0.001 ≤ z ≤ 0.100 (for example, z is a range of 0.001, 0.005, 0.01, 0.05, 0.1 or any of the above values), where A includes one or more elements from families IA, IIA, IIIA, IVA, VA, IIB, IVB, VB, VIB, and VIII, and Q includes one or more elements from families IIIA, IVA, VA, VIA, and VIIA.
[0083] In some embodiments, M1 includes one or more elements selected from Mn and Al; and / or,
[0084] The M2 includes one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb; and / or,
[0085] The R includes one or more elements selected from N, F, S, and Cl; and / or,
[0086] One or more coating layers in the positive electrode material A independently include one or more of Al2O3, ZrO2, TiO2, and Li3PO4; and / or,
[0087] The A includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and may optionally include one or more elements selected from Fe, Ti, V, Ni, Co, and Mg; and / or,
[0088] The Q includes one or more elements selected from B, Si, N, S, F, Cl, and Br, and may optionally include one or more elements selected from B, Si, N, and S.
[0089] [Positive electrode plate]
[0090] A positive electrode typically includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including the aforementioned positive electrode material composition.
[0091] Therefore, a positive electrode sheet is prepared by mixing micron-sized positive electrode material A with submicron or nano-sized positive electrode material B. When the proportion of positive electrode material A in the total weight of the positive electrode material is greater than or equal to 50% and less than 100%, the Dv50 particle size of positive electrode material B, within the above range, solves the problem of excessively small material particles and excessive micro powder. The ratio of the Dv50 particle size of positive electrode material A to that of positive electrode material B, within the above range, reduces the number of small particles on the electrode surface sticking to the pressure roller during cold pressing. The weight proportion of the coating layer of positive electrode material A, within the above range, increases the surface roughness of the material, improves the mutual adhesion between material particles, reduces the degree of sticking to the roller during cold pressing, thereby increasing the actual thickness of the positive electrode sheet and thus increasing the battery capacity. When the proportion of positive electrode material A in the total weight of the positive electrode material is greater than 0 and less than 50%, there is no problem of sticking to the roller during cold pressing.
[0092] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of cathode materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before feeding. When the cathode material is applied to the battery system, the molar Li content changes after charge-discharge cycles.
[0093] In the examples of cathode materials in this application, the molar content of O is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.
[0094] In some embodiments, the positive electrode sheet also includes a binder;
[0095] When the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the weight percentage of the binder in the positive electrode sheet is 1.2%-1.8%, for example, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, or any range of the above values;
[0096] When the weight percentage of the positive electrode material A in the positive electrode active material composition is greater than 0 and less than 50%, the weight percentage of the binder in the positive electrode sheet is 1.9%-2.3%, for example, 1.9%, 2.0%, 2.1%, 2.2%, 2.3% or any of the above values.
[0097] Therefore, when the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, using the above-mentioned weight percentage of the binder is beneficial to improving the brittleness of the positive electrode sheet while maintaining the interparticle bonding effect. When the weight percentage of the positive electrode material A in the positive electrode active material composition is greater than 0 and less than 50%, increasing the amount of binder to the above range can improve the bonding effect between the two positive electrode material particles and increase the actual thickness of the positive electrode sheet.
[0098] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0099] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0100] In some embodiments, as an example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0101] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0102] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0103] [Negative electrode plate]
[0104] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0105] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0106] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0107] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0108] In some embodiments, the negative electrode film layer may optionally include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0109] In some embodiments, the negative electrode film may optionally include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0110] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0111] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0112] [Electrolytes]
[0113] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0114] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.
[0115] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0116] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0117] In some embodiments, the electrolyte may optionally include additives. As examples, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0118] [Isolation membrane]
[0119] In some embodiments, the battery cell also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0120] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0121] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0122] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0123] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0124] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 The example shown is a square-structured battery cell 5.
[0125] In some implementations, refer to Figure 2 The outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 can be placed over the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The number of electrode assemblies 52 contained in a single battery cell 5 may be one or more, which can be selected by those skilled in the art according to specific practical needs.
[0126] In some implementations, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0127] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0128] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0129] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0130] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0131] In addition, this application also provides an electrical device, which includes at least one of the battery cell, battery module, or battery pack provided in this application. The battery cell, battery module, or battery pack can be used as the power source of the electrical device or as the energy storage unit of the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0132] As an electrical device, you can choose individual battery cells, battery modules, or battery packs according to your usage requirements.
[0133] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of individual battery cells, a battery pack or battery module can be used.
[0134] [Example]
[0135] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0136] Example 1
[0137] The core LiNi of cathode material A 0.55 Co 0.5 Mn 0.4 O2, coating layer is TiO2 (purchased from Guangdong Bangpu Recycling Technology Co., Ltd.), the weight content of the coating layer in cathode material A is 2800 ppm, the Dv50 particle size of cathode material A is 3.9 μm, and the BET specific surface area of cathode material A is 0.74 m². 2 / g; Cathode material B is LiMn 0.6 Fe 0.4 PO4, carbon coating (purchased from Shenzhen Defang Nanotechnology Co., Ltd.), the Dv50 particle size of cathode material B is 0.8 μm, and the BET specific surface area of cathode material B is 13.8 m². 2 / g;
[0138] Positive electrode materials A and B (weight ratio 7:3), binder polyvinylidene fluoride (PVDF), and conductive agent conductive carbon are added to a certain amount of N-methylpyrrolidone (NMP). The weight ratio of positive electrode materials, binder, and conductive agent is 96:1.5:2.5. The mixture is stirred in a drying room to form a uniform slurry with a viscosity controlled at 3000-10000 mPa·s. The slurry is then coated onto aluminum foil and dried to form a positive electrode sheet.
[0139] Examples 2-49 and Comparative Examples 1-3 were prepared using methods similar to those of Example 1, with different product parameters detailed in Table 1.
[0140] The cathode material A used in Examples 2-49 and Comparative Examples 1-3 was purchased from Guangdong Bangpu Recycling Technology Co., Ltd.
[0141] The cathode material B used in Examples 2-49 and Comparative Examples 1-3 was purchased from Shenzhen Defang Nanotechnology Co., Ltd.
[0142]
[0143]
[0144]
[0145]
[0146] Testing of materials and batteries
[0147] (1) Dv50 particle size test:
[0148] Take an appropriate amount of sample, add 20 mL of deionized water, and sonicate for 5 minutes (53 kHz, 120 W) to completely disperse the sample. Use a laser particle size analyzer (MasterSizer2000) to determine the Dv50 particle size of the material.
[0149] (2) Test of BET specific surface area:
[0150] The nitrogen adsorption specific surface area was tested using the nitrogen adsorption specific surface area analysis method and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis test can be performed using the TriStar II specific surface area and porosity analyzer from Micromeritics, USA. The test procedure can refer to GB / T 19587-2004.
[0151] The detailed steps are as follows: Dry the sample to be tested in a vacuum drying oven at 200℃ for 2 hours; weigh 1g of the sample to be tested and place it in the test tube; fill the liquid nitrogen cup with liquid nitrogen and insert it into the test tube; use nitrogen as the adsorption gas; plot the adsorption-desorption curve with relative pressure P / P0 of 0 to 0.99 using a specific surface area and porosity analyzer; P is the equilibrium adsorption pressure and P0 is the saturated vapor pressure; calculate the BET specific surface area of the positive electrode active material using the BET method.
[0152] (3) Cold pressing roller sticking test:
[0153] Multiple positive electrode sheets were taken and cold-pressed on the production line with different cold-pressing pressures. The transmission rate of the positive electrode sheets on the production line was 50m / min, and the cold-pressing pressure was applied to extend the length of the positive electrode sheets by 0.4% for subsequent testing.
[0154] Using a positive electrode sheet cold-pressed under selected pressure and blank aluminum foil, a stamping machine is used to obtain a coated electrode sheet and a blank aluminum foil sheet with a radius of 7mm. The mass of the coated electrode sheet is m1, and the mass of the blank aluminum foil sheet is m2. Therefore, the coating weight per unit area of aluminum foil is (m1-m2) / (π×0.7). 2 (Unit: g / cm³) 2 The thickness of the coated electrode and the blank aluminum foil were measured multiple times using a micrometer, and the average values were taken to obtain the average thickness of the coated electrode and the average thickness of the blank aluminum foil. The compaction density P of the positive electrode was calculated according to the following formula, with the unit being g / cm³. 3 .
[0155] The compaction density P of the positive electrode sheet = coating weight per unit area of aluminum foil / (average thickness of the coated electrode sheet - average thickness of the blank aluminum foil sheet)
[0156] The theoretical thickness (in cm) and lower limit of thickness (in mm) of the positive electrode sheet after cold pressing are calculated according to the following formula.
[0157] The theoretical thickness of the positive electrode sheet after cold pressing = (m1 - m2) / (II × 0.7) 2 ) / P
[0158] The lower limit of the thickness of the positive electrode sheet after cold pressing = the theoretical thickness of the positive electrode sheet after cold pressing × 10 - 0.002
[0159] The positive electrode sheet was selected to be cold-pressed for 10,000 m length. The last 10 m of the positive electrode sheet was tested. The thickness of the positive electrode film (excluding the aluminum foil thickness) at the center of the width direction was measured every 0.5 m along the length direction using a micrometer. The average value of multiple measurements is the actual thickness H of the positive electrode sheet after cold pressing.
[0160] If the actual thickness H of the positive electrode sheet after cold pressing is equal to the theoretical thickness of the positive electrode sheet after cold pressing, then no sticking to the cold pressing roller will occur.
[0161] If the actual thickness H of the cold-pressed positive electrode sheet is greater than or equal to the lower limit of the thickness of the cold-pressed positive electrode sheet but less than the theoretical thickness of the cold-pressed positive electrode sheet, then slight cold-pressing roller sticking occurs, which is acceptable (referred to as roller sticking in the table).
[0162] If the actual thickness H of the positive electrode sheet after cold pressing is less than the lower limit of the thickness of the positive electrode sheet after cold pressing, severe cold pressing roller sticking will occur, which is unacceptable.
[0163] (4) Brittleness test of the positive electrode sheet:
[0164] The positive electrode sheet, after being cold-pressed using the pressure selected in item (3), is placed in an environment with 2% relative humidity and dried for 2 hours. Then, the positive electrode sheet is folded in half along its length. If the positive electrode sheet breaks brittle after folding, it is recorded as 0 times; if it does not break brittle, it is recorded as 1 time. Then, it is folded in the opposite direction (the folding position is the same as the first time). If it breaks brittle, it is recorded as 1 time; if it does not break brittle, it is recorded as 2 times. The above method is repeated until the electrode sheet breaks brittle. The count is equal to the number of tests - 1.
[0165] The test results are shown in Table 2.
[0166] Table 2: Performance test results of Examples 1-49 and Comparative Examples 1-3
[0167]
[0168]
[0169]
[0170] Based on the above results, we can conclude that:
[0171] Compared with Comparative Example 1, where the coating layer accounts for less than 1800 ppm by weight in cathode material A, Examples 1-31 of this application significantly improve the cold-pressing adhesion of the cathode sheet.
[0172] Compared with Comparative Example 2, where the Dv50 particle size of cathode material B is less than 0.4 μm and the ratio of Dv50 particle size of cathode material A to cathode material B is greater than 11.25, Examples 1-31 of this application significantly improve the cold pressing sticking degree of the cathode sheet.
[0173] Compared with the positive electrode material A of Comparative Example 3, which does not include a coating layer, Examples 1-31 of this application significantly improve the degree of cold pressing and sticking of the positive electrode sheet.
[0174] Compared with Examples 10 and 15-21, Examples 1-3 and 5 of this application use a Dv50 particle size ratio of 3.5-5 for positive electrode material A and positive electrode material B to further improve the cold pressing sticking degree of the positive electrode sheet.
[0175] Compared with Examples 10 and 15-16, Examples 1-2 and 5 of this application use positive electrode material B with a Dv50 particle size of 0.8-0.9μm to further improve the cold pressing sticking degree of the positive electrode sheet.
[0176] Compared with Examples 17-18, the cathode material A used in Examples 10 and 19-20 of this application has a Dv50 particle size of 3.5-3.9 μm and a BET of 0.74-0.9 μm. 2 / g, the actual thickness of its positive electrode sheet is closer to the theoretical thickness of the electrode sheet, indicating that the degree of sticking to the roller during cold pressing is further reduced.
[0177] Examples 8-12 of this application show that as the proportion of cathode material A in the total weight of cathode material increases from 50% to 90%, the brittleness of the cathode sheet gradually improves.
[0178] Examples 32-49 of this application show that the particle size of the positive electrode material A is in the micrometer range, and the particle size of the positive electrode material B is in the submicrometer or nanometer range. When the weight percentage of the positive electrode material A is greater than 0 and less than 50%, the positive electrode sheet does not have a roller sticking problem.
[0179] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A cathode material composition comprising cathode material A and cathode material B, wherein cathode material A and cathode material B are independently single-crystal materials or near-single-crystal materials; When the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the particle size of the positive electrode material A particles is in the micrometer range, the particle size of the positive electrode material B particles is in the submicrometer or nanometer range, the ratio of the Dv50 particle size of the positive electrode material A particles to the Dv50 particle size of the positive electrode material B particles is 3.5-11.25, the Dv50 particle size of the positive electrode material B particles is 0.4-1 μm, and the positive electrode material A includes a core and one or more coating layers covering the core, the total weight of the coating layers accounts for 1800 ppm-4000 ppm of the weight of the positive electrode material A; When the weight percentage of the positive electrode material A in the positive electrode material composition is greater than 0 and less than 50%, the particle size of the positive electrode material A particles is in the micrometer range, and the particle size of the positive electrode material B particles is in the submicrometer or nanometer range.
2. The cathode material composition according to claim 1, wherein, When the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the Dv50 particle size of the positive electrode material A particles is 3.5-4.5 μm.
3. The cathode material composition according to claim 1, wherein, When the weight percentage of the positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the BET specific surface area of the positive electrode material A is 0.6 - 0.9 m². 2 / g, and / or, the BET specific surface area of the cathode material B is 9.4-15.5 m² / g. 2 / g.
4. The cathode material composition according to claim 1, wherein the weight percentage of cathode material A in the cathode material composition is greater than or equal to 50% and less than 100%, The ratio of the Dv50 particle size of the positive electrode material A particles to the Dv50 particle size of the positive electrode material B particles is 3.5-5; and / or, The Dv50 particle size of the cathode material B particles is 0.8-1 μm; and / or, The total weight of the coating layer accounts for 2000 ppm - 2800 ppm of the weight of the cathode material A; and / or, The positive electrode material A particles have a Dv50 particle size of 3.5-4 μm; and / or, The BET specific surface area of the cathode material A is 0.74 - 0.9 m². 2 / g, and / or, The BET specific surface area of the cathode material B is 11-15.5 m². 2 / g.
5. The cathode material composition according to any one of claims 1 to 4, wherein, The positive electrode material A is a layered positive electrode material, and / or the positive electrode material B is a polyanion positive electrode material.
6. The cathode material composition according to claim 1, wherein, The positive electrode material A includes a core and one or more coating layers covering the core, and the core comprises the compound Li a Ni b Co c M1 d M2 e O f R g , the one or more coating layers independently include one or more of oxides and phosphates; where 0.75≤a≤1.2, 0<b<1, 0<c<1, 0<d<1, 0≤e≤0.2, 1≤f≤2.5, 0≤g≤1, f+g≤3, the M1 includes one or more elements from Group IIIA and Group VIIB, the M2 includes one or more elements from Group IIA, Group VA, Group IB, Group IIB, Group IIIB, Group IVB, Group VB, Group VIB and Group VIII, and the R includes one or more elements from Group VA, Group VIA and Group VIIA.
7. The cathode material composition according to claim 1, wherein, When the weight proportion of the positive electrode material A in the positive electrode material composition is greater than 0 and less than 50%, the positive electrode material A includes the compound Li a Ni b Co c M1 d M2 e O f R g , wherein 0.75≤a≤1.2, 0<b<1, 0<c<1, 0<d<1, 0≤e≤0.2, 1≤f≤2.5, 0≤g≤1, f+g≤3, the M1 includes one or more elements from Group IIIA and Group VIIB, and the M2 includes one or more elements from Group IIA, Group VA, Group IB, Group IIB, Group IIIB, Group IVB, Group VB, Group VIB and Group VIII, the R includes one or more elements from Group VA, Group VIA and Group VIIA.
8. The cathode material composition according to claim 1, wherein, The cathode material B includes the compound Li. 1+x Mn 1- y A y P 1-z Q z O4, wherein -0.100≤x≤0.100, 0.001≤y≤0.800, 0≤z≤0.100, and A includes one or more elements from families IA, IIA, IIIA, IVA, VA, IIB, IVB, VB, VIB, and VIII, and Q includes one or more elements from families IIIA, IVA, VA, VIA, and VIIA.
9. The cathode material composition according to claim 1, wherein, The cathode material B comprises a core and one or more coating layers covering the core, the core comprising the compound Li. 1+x Mn 1-y A y P 1-z Q z O4, wherein the one or more coating layers independently comprise one or more of pyrophosphate, phosphate, and carbon; wherein -0.100≤x≤0.100, 0.001≤y≤0.800, 0.001≤z≤0.100, A comprises one or more elements from Groups IA, IIA, IIIA, IVA, VA, IIB, IVB, VB, VIB, and VIII, and Q comprises one or more elements from Groups IIIA, IVA, VA, VIA, and VIIA.
10. The cathode material composition according to claim 6 or 7, wherein, The M1 includes one or more elements selected from Mn and Al; and / or, The M2 includes one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb; and / or, The R includes one or more elements selected from N, F, S, and Cl.
11. The cathode material composition according to claim 6, wherein, One or more coating layers in the cathode material A independently include one or more of Al2O3, ZrO2, TiO2 and Li3PO4.
12. The cathode material composition according to claim 8 or 9, wherein, The A includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge; and / or, The Q includes one or more elements selected from B, Si, N, S, F, Cl, and Br.
13. A positive electrode sheet comprising the positive electrode material composition according to any one of claims 1 to 12.
14. The positive electrode sheet according to claim 13, further comprising a binder; When the weight percentage of positive electrode material A in the positive electrode material composition is greater than or equal to 50% and less than 100%, the weight percentage of the binder in the positive electrode sheet is 1.2% - 1.8%. When the weight percentage of positive electrode material A in the positive electrode material composition is greater than 0 and less than 50%, the weight percentage of the binder in the positive electrode sheet is 1.9% - 2.3%.
15. A battery comprising a positive electrode material composition according to any one of claims 1-12 or a positive electrode sheet according to claim 13 or 14.
16. An electrical device comprising the battery of claim 15.
Citation Information
Patent Citations
Multi-element positive electrode material as well as preparation method and application thereof
CN114927659A
Positive Electrode for Lithium Secondary Battery and Positive Electrode and Lithium Secondary Battery Comprising the Same
US20240030428A1